Tick-borne Great Island Virus: (I) Identification of seabird host and evidence for co-feeding and viraemic transmission. - Nunn, M; Barton, T; Wanless, S; Hails, R; Harris, M; Nuttall, P (2006)
Great Island Virus (GIV) is an arbovirus present in the tick Ixodes uriae, a common ectoparasite of nesting seabirds. Common guillemot (Uria aalge) and black-legged kittiwake (Rissa tridactyla) are the preferred and most abundant hosts of I. uriae on the Isle of May, Scotland. As part of a study to understand the epidemiology of GIV, the ability of guillemot and kittiwake to support tick-borne transmission of GIV was examined. GIV was present in ticks feeding in isolated guillemot colonies and guillemots had virus-specific neutralizing antibodies demonstrating previous GIV infection. By contrast, only uninfected ticks were found in colonies inhabited solely by kittiwakes. GIV was isolated from kittiwake ticks in colonies which also contained breeding guillemots but no virus-specific neutralizing antibodies were present in blood samples of kittiwake on which infected ticks were feeding. Thus guillemots are the main vertebrate hosts of GIV on the Isle of May whereas kittiwakes do not appear to be susceptible to infection. Virus infection of adult ticks feeding on guillemots was highly efficient and may involve both viraemic transmission and transmission from infected to uninfected ticks feeding together on birds that do not develop a patent viraemia.